2003
DOI: 10.1034/j.1600-0447.2003.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

A 20‐year follow‐up study on schizophrenia in Singapore

Abstract: Most patients with schizophrenia had a good/fair outcome at 20 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 31 publications
4
36
0
1
Order By: Relevance
“…Our sample and that of Wiersma et al 18 (20.4%) in the Netherlands showed one of the smallest proportions of subjects with some form of employment at study end (25.6%). In contrast, Kua et al 26 reported that 88% were employed in Singapore and emphasised the importance of work in their culture. Higher unemployment rates in the general population (for example, compared with the province of Alberta whose economy was stronger with less unemployment than Quebec) 5 could also be hypothesized, along with a more generous unemployment benefits program in Canada, which does not encourage people with partial invalidity to get a job.…”
Section: Is Outcome Really Negative?mentioning
confidence: 96%
See 3 more Smart Citations
“…Our sample and that of Wiersma et al 18 (20.4%) in the Netherlands showed one of the smallest proportions of subjects with some form of employment at study end (25.6%). In contrast, Kua et al 26 reported that 88% were employed in Singapore and emphasised the importance of work in their culture. Higher unemployment rates in the general population (for example, compared with the province of Alberta whose economy was stronger with less unemployment than Quebec) 5 could also be hypothesized, along with a more generous unemployment benefits program in Canada, which does not encourage people with partial invalidity to get a job.…”
Section: Is Outcome Really Negative?mentioning
confidence: 96%
“…30 Different outcome dimensions show more stability after 5 years of evolution, replicating data in other studies from different decades. 19,26,31,32 As discussed by Harrison et al,19 this raises the hypothesis of a critical window for therapeutic interventions, as the early psychosis intervention movement now purports.…”
Section: Course Of Illness and Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…La esquizofrenia también se asocia a un riesgo elevado de suicidio y el Standard Mortality Rate por suicidio varía entre el 15,7 15 y el 39,7 16 . El porcentaje de sujetos con diagnóstico de esquizofrenia que cometen suicidio a lo largo de su vida también varía notablemente, desde el 4,9 17 al 9,7% según distintos estudios 18 .…”
Section: Introductionunclassified